Envelopamento da tropopausa no sul da América do Sul: relações entre a corrente de jato em altos níveis e a coluna total de ozônio - Fontinele, José Lourêdo (2012)
This study discusses the influence of tropopause folding in ozone total column during the passage of frontal systems. This research aims to analyze, from the relations between the upper level jet and the ozone total column, tropopause folding in southern South America. The aim is also to quantify the cold fronts that have acted throughout 2008, as well as identify them in tropopause folding events and action of the jet stream. Finally, it verifies the occurrence of stratospheric air into the troposphere at selected events. This research is characterized by being predominantly qualitative in relation to the collection and analysis of data obtained from Brewer Spectrophotometers, installed at the Southern Space Observatory, and the Ozone Monitoring Instrument (OMI). It is noteworthy that were initially selected all events of cold fronts that occurred in 2008. However, only events of greater magnitude were analyzed and the chosen were the ones that evidenced a strong tropopause folding. Of the results analyzed, we can conclude that the ozone total column is influenced by the passage of fronts and may increase when there is intrusion of stratospheric air in the troposphere through the tropopause folding, caused by the action of the jet stream that comes with the front.